Model Testing of the Factors That Influence Performance of Function Focused Care and Function Among Assisted Living Residents. (February 2022) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Fix, Steven; Holmes, Sarah; Zhu, Shijun
The purpose of this study was to test a model of factors associated with participating in function focused care. Function focused care is a philosophy of care in which residents are encouraged to engage in functional and physical activities during care interactions. This was a secondary data analysis using data from the Dissemination and Implementation of Function Focused Care for Assisted Living Using the Evidence Integration Triangle (FFC-AL-EIT) study. Residents ( n = 550) were recruited from 59 AL settings. The majority were female ( n = 380, 69%) and White ( n = 536, 97%). Model testing was done. Comorbidities, quality of interactions, environments, profit status, cognitive impairment, depression, and function were associated with function focused care and accounted for 17% of the variance. Next steps should include intervening on changeable factors (e.g., environments) and adding factors to better explain performance of function focused care such as motivation, resilience, and staff satisfaction.